Providers' approaches to contraceptive provision in Cape Town - Fataar, Kulthum; Zweigenthal, Virginia; Harries, Jane (Frontiers in Global Women's Health, 2022)
Background: Health care providers can play a significant role in empowering women to make informed decisions when selecting suitable contraceptive methods during contraceptive counselling. This study explores primary care providers’ perspectives and approaches to contraceptive service provision for women attending public sector clinics in South Africa, with the intention of ascertaining established practices and training needs. Methods: Ten in-depth interviews were conducted at five primary health care facilities in urban areas in Cape Town, South Africa. Eligible participants included nurses providing contraceptive services and willing to participate in the study. The qualitative software package NVivo was used to sort and manage data. Data was analyzed using a thematic analysis approach. Results: Overall, providers emphasized supporting women in contraceptive decision-making. Sexual and reproductive health training increased providers confidence to deliver appropriate contraceptive services. Contraceptive prescribing practices were influenced by women’s medical history and preferred bleeding patterns. Providers’ concerns about adherence to methods for younger women and suspected adverse events for older women impacted on prescribing. Challenges experienced when providing contraceptive services included: contraceptive stockouts; time constraints of employed women accessing the service; and their work pressure due to providing other health services. Discussion: Health care providers play a critical role in facilitating women’s right to access high quality contraceptive services. Providers saw themselves as negotiators during contraceptive counselling. They considered both women’s preferences and their own recommendations for contraception, to provide information that would enable women to make informed contraceptive decisions. By reinforcing this approach to contraceptive counselling and focusing on shared decision-making, should encourage autonomy in method selection and limit the influence of provider’s contraceptive method selection.